Investigating surface movements of debris-covered Miage glacier, Western Italian Alps, using dendroglaciological analysis - M. Pelfini; M. Santilli; G. Leonelli; M. Bozzoni (Journal of Glaciology, 2007)
Dendroglaciological analysis of supraglacial trees represents an example of applied dendrogeornorphological methods in reconstructing glacier variations. Supraglacial trees react to glacier ice and debris movement, assuming typical shapes with modified radial growth. In this paper, based on tree-ring analysis of Larix decidua Mill., we investigate the relationship between the distribution and growth of trees located on the most famous and representative debris-covered glacier in the Italian Alps (Miage glacier, Valle d'Aosta) and the superficial movements of ice and debris in the lower part of the tongue. Different growth anomalies (e.g. pointer years, compression wood, abrupt growth changes) were identified and dated. Three reference tree-ring chronologies based on undisturbed larches growing outside the glacier were constructed for comparison with tree-ring data from supraglacial trees. The oldest sampled trees colonized the glacier surface just before 1960. The simultaneous presence of different disturbance indicators occurred mainly between 1984 and 1990 on the southern lobe and during the period 1989-93 on the northern glacier lobe. These results fit with glaciological data documenting volume and surface-level variations in the same period.